Female Entrepreneurship: Types of Economic Activity - Pinkovetskaia, Iuliia S.; Kryukova, Liudmila I.; Arbeláez Campillo, Diego Felipe; Rojas-Bahamon, Magda Julissa (Journal of History Culture and Art Research, 2019)
In recent years women entrepreneurs have made a significant contribution to the economic growth of most countries. Therefore, at the present stage of the entrepreneurship study, it is relevant to analyze the patterns that characterize the current level of women’s entrepreneurial activity as well as determine the sectoral structure of women’s entrepreneurship. The purpose of the study is a comprehensive assessment of women’s early entrepreneurial activity and their sectoral preferences in creating their own business. In the course of the study, the results of the report on the global monitoring project for female entrepreneurship for the years 2016-2017 as to 74 countries is used. The levels of entrepreneurial activity of women in these countries also reviewed. The sectoral structure of women’s entrepreneurship was assessed in five groups including typical types of economic activity by using normal density distribution functions. According to the results of the researches, conclusions were drawn on the predominance of such types of economic activity as trade (46.54%), health care, education and social services (19.22%), management and personal services as (15.70%). The obtained results can be used by entrepreneurs as well as by government bodies related to the business activities regulation. In the article, the original tools for assessing the sectoral structure of women’s entrepreneurship is proposed.